2016
DOI: 10.1111/pde.12731
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyomatous Mesenchymal Hamartoma: A Deep Subcutaneous Lesion in the Sternoclavicular Area

Abstract: Cutaneous rhabdomyomatous mesenchymal hamartoma (RMH) is a rare benign tumor composed of two or more types of mesenchymal-derived cells. RMHs are generally sporadic and independent, but they can be associated with congenital abnormalities. We report a subcutaneous case of RMH in the sternoclavicular area with two recurrences after complete surgical excision. The course is variable and can range from spontaneous resolution to repeated recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 4 publications
0
29
0
Order By: Relevance
“…In a report of twenty‐four patients with RMH, six (25%) had associated congenital anomalies, including cleft lip and palate, ocular anomalies, digit anomalies, thyroglossal duct sinus, and Delleman's syndrome . Although a few cases of RMH associated with IH have been reported, to the best of our knowledge RMH has never been reported in association with PHACE syndrome . In this series, we report the new association of RMH with PHACE syndrome.…”
Section: Discussionmentioning
confidence: 77%
“…In a report of twenty‐four patients with RMH, six (25%) had associated congenital anomalies, including cleft lip and palate, ocular anomalies, digit anomalies, thyroglossal duct sinus, and Delleman's syndrome . Although a few cases of RMH associated with IH have been reported, to the best of our knowledge RMH has never been reported in association with PHACE syndrome . In this series, we report the new association of RMH with PHACE syndrome.…”
Section: Discussionmentioning
confidence: 77%
“…) . The etiology of SMH is unclear, although it has been suggested that an abnormality in the migration of embryonic mesodermal tissues may be involved . The cause of regression of SMH is also unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, treatment has consisted of surgical excision, but SMH resembling scleroderma en coup de sabre of the chin and a subcutaneous SMH in the sternoclavicular area recurred after surgical excision .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations